Needs Assessment of Safe Medicines Management for Older People With Cognitive Disorders in Home Care: An Integrative Systematic Review - Vaismoradi, Mojtaba; Behboudi-Gandevani, Samira; Lorenzl, Stefan; Weck, Christiane; Paal, Piret (Frontiers in Neurology, 2021)
Background and objectives: The global trend of healthcare is to improve the quality and safety of care for older people with cognitive disorders in their own home. There is a need to identify how medicines management for these older people who are cared by their family caregivers can be safeguarded. This integrative systematic review aimed to perform the needs assessment of medicines management for older people with cognitive disorders that receive care by their family caregivers in their own home. Methods: An integrative systematic review of the international literature was conducted to retrieve all original qualitative and quantitative studies that involved the family caregivers of older people with cognitive disorders in medicines management in their own home. MeSH terms and relevant keywords were used to search on four online databases of PubMed (Including Medline), Scopus, Cinahl, and Web of Science and to retrieve studies published up to March 2021. Data were extracted by two independent researchers and the review process was informed by the PRISMA. Given that selected studies were heterogeneous in terms of the methodological structure and research outcomes, a meta-analysis could not be performed. Therefore, narrative data analysis and knowledge synthesis were performed to report the review results. Results: The search process led to retrieving 1241 studies, of which 12 studies were selected for data analysis and knowledge synthesis. They involved 3890 older people with cognitive disorders and 3465 family caregivers. Their methodologies varied and included cohort, randomised controlled trial, cross-sectional, grounded theory, qualitative framework analysis, and thematic analysis. The pillars that supported safe medicines management with the participation of family caregivers in home care consisted of the interconnection between older people’s needs, family caregivers’ role, and collaboration of multidisciplinary healthcare professionals. Conclusion: Medicines management for older people with cognitive disorders is complex and multidimensional. This systematic review provides a comprehensive image of the interconnection between factors influencing the safety of medicines management in home care. Considering that home-based medicines management is accompanied with stress and burden in family caregivers, multidisciplinary collaboration between healthcare professionals is essential along with the empowerment of family caregivers through education and support.